Role of fibrinolysis and interventional therapy for acute venous thromboembolism - Emmerich, Joseph; Meyer, Guy; Decousus, Hervé; Agnelli, Giancarlo (Thrombosis and Haemostasis, 2006)
The initial goals of treatment for venous thromboembolism (VTE) are usually achieved with anticoagulation. This reviewfocuses on fibrinolysis and interventional therapy in VTE, treatments whose indications are much more controversial. The benefit-to-risk ratio of fibrinolysis in deep vein thrombosis (DVT) is dubious. Thrombolytic treatment is recommended forunstable patients with pulmonary embolism (PE), although these patients represent less than 5% of all patients hospitalized for PE. The use of thrombolytic treatment in patients with sub-massive PE remains controversial. Two indications are widely recognized for inferior vena cava filters: the first isa permanent or temporary contraindication to anticoagulation, in patients with proximal DVT or PE. The second is the occurrence of PE or propagation of the thrombus in patients treated for DVT or recurrence in patients with PE. The PREPIC study demonstrated that in acute VTE, vena cava filters reduced the risk of PE but increased that of DVT and had no effect on survival. The fact that prevention of PE is mainly observed during the short initial period following the diagnosis of an acute VTE event justifies a new randomized study with the use of retrievable filters as an adjuvant to anticoagulation in high risk patients with PE.
Keywords: Deep vein thrombosis; pulmonary embolism; ibrinolysis; thrombolysis; inferior vena cava filter